Effect of Supplimenting Black Seeds (Nigella Sativa Linn) in the Ration on the Immune Response of Newcastle Disease and Some Physiological Aspects of Broiler Chicken: Atheer Kassab , Aamer Rassam - Kassab, Atheer (The Iraqi Journal of Veterinary Medicine, 2005)
The study was conducted to investigate the role of supplementing the diet ofbroiler chicken with Black seed (Nigella sativa Linn) broiler chicken in theimmune response of the bird .The study has also investigated the level of someserum proteins and the activity of amino group transmitting enzymes. The Blackseeds have been ground and supplemented in the diet of the chickens at 2%inclusion rate .A total of 80 Faobro broiler chicks were divided equally into 4groups.Group 1: given Black seed supplemented diet and vaccinated at 8 ,16 and 26 daysof age with one dose of live Newcastle (ND) vaccine in the crop and injected 0.2ml oil adjuvant ND vaccine subcutaneously.Group 2: given Black seed supplemented diet and vaccinated at 8 ,16 and 26 daysof age with one dose of live Newcastle (ND) vaccine in the crop but did notinjected with oil adjuvant ND vaccine.Group 3: A control to group 1, but not supplemented with Black seed in the diet.Group 4: A control to group 2, but not supplemented with Black seed in the diet.Results showed that the supplementation of Black seed with the diet causedsignificant increase in the total serum protein, the serum globuline, the NDantibody examined by Haemagglutination test and the body weight. Thedifferences were more obvious when the birds were vaccinated with oil adjuvantvaccine .The enzyme Aspartate aminotransferase (AST) and Alanineaminotransferase(ALT) have not been affected by the inclusion of 2% Black seedin the diet. It was concluded that the inclusion of 2% Black seed in the diet hasled to a better immune response and health conditions shown by the birds.